2012
DOI: 10.1021/jf303044a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pasteurization on the Protein Composition and Oxidative Stability of Beer during Storage

Abstract: The impacts of pasteurization of a lager beer on protein composition and the oxidative stability were studied during storage at 22 °C for 426 days in the dark. Pasteurization clearly improved the oxidative stability of beer determined by ESR spectroscopy, whereas it had a minor negative effect on the volatile profile by increasing volatile compounds that is generally associated with heat treatment and a loss of fruity ester aroma. A faster rate of radical formation in unpasteurized beer was consistent with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
3
17
3
Order By: Relevance
“…The staling ketone β ‐damascenone was found to increase in all beers, which was also the case for the ethyl ester and staling compound ethyl phenylacetate, which actually decreased in concentration during pasteurization. The staling ketone 4‐methyl‐2‐pentanone was uninfluenced by storage in both pasteurized and non‐pasteurized beer, but was previously found to increase in pasteurized filtered beer during storage at 22°C . Only a slight increase in the fatty acid oxidation product hexanal during storage was detected and no other fatty acid oxidation products were detected, including ( E )‐2‐nonenal and methional; however, the concentration of ( E )‐2‐nonenal may have been below our detection limit.…”
Section: Resultscontrasting
confidence: 52%
See 3 more Smart Citations
“…The staling ketone β ‐damascenone was found to increase in all beers, which was also the case for the ethyl ester and staling compound ethyl phenylacetate, which actually decreased in concentration during pasteurization. The staling ketone 4‐methyl‐2‐pentanone was uninfluenced by storage in both pasteurized and non‐pasteurized beer, but was previously found to increase in pasteurized filtered beer during storage at 22°C . Only a slight increase in the fatty acid oxidation product hexanal during storage was detected and no other fatty acid oxidation products were detected, including ( E )‐2‐nonenal and methional; however, the concentration of ( E )‐2‐nonenal may have been below our detection limit.…”
Section: Resultscontrasting
confidence: 52%
“…Storage influenced the protein composition of beer 2, resulting in the loss of a number of protein bands and formation of a few new protein bands, while storage only had a minor effect on protein composition of beer 1. In beer 2 protein Z (the strongest band just above the 36.5 kDa marker) is suggested to be degraded by protease activity from the yeast as the additional bands appearing below protein Z in the stored beers previously have been identified as protein Z . The band appearing just below the 14.4 kDa marker has previously been identified to contain trypsin/ α ‐amylase inhibitor and LTP1 , and this band was also lost during storage, which was also likely to be due to protease activity of the yeast.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, He et al (2012) observed around 10% lower antioxidant activity in fresh cloudy wheat beer over the first 18 days of storage at 20°C. Lund et al (2012) and Hoff et al (2013) showed that the radical formation during storage occurs faster in unpasteurised than in pasteurised beer, and that beer pasteurisation greatly improves oxidative stability. However, Cao et al (2011) observed that if pasteurization intensity is too severe, this may result in lower polyphenol content and reduced oxidative stability.…”
Section: Resultsmentioning
confidence: 99%